Radiative impact of Etna volcanic aerosols over south eastern Italy on 3 December 2015. (June 2018) - Romano, S.; Burlizzi, P.; Kinne, S.; De Tomasi, F.; Hamann, U.; Perrone, M.R.
Abstract: Irradiance and LiDAR measurements at the surface combined with satellite products from SEVIRI (Spinning Enhanced Visible and InfraRed Imager) and MODIS (MODerate resolution Imaging Spectroradiometer) were used to detect and characterize the Etna volcano (Italy) plume that crossed southeastern Italy on 3 December 2015, from about 10:00 up to 11:30 UTC, and estimate its radiative impact. The volcanic plume was delivered by a violent and short paroxysmal eruption that occurred from 02:30 to 03:10 UTC of 3 December 2015, about 400 km away from the monitoring site. Measurements from the LiDAR combined with model results showed that the aerosol optical depth of the volcanic plume, located from about 11 to 13 km above sea level (asl), was equal to 0.80 ± 0.07 at 532 nm. A low tropospheric aerosol load, located up to about 7 km asl, with optical depth equal to 0.19 ± 0.01 at 532 nm was also revealed by the LiDAR measurements. Short-Wave (SW) downward and upward irradiance measurements revealed that the instantaneous SW direct radiative forcing at the surface ( DRF surf ) decreased to −146 ± 16 W m −2 at 10:50 UTC because of the volcanic plume passage. A Two-Stream radiative transfer model integrated with experimental measurements, which took into account the volcanic plume and the low tropospheric aerosol properties, was used to reproduce the SW radiative flux measurements at the surface and estimate the aerosol DRF both at the top of the atmosphere (TOA) and at the surface, in addition to the aerosol heating rate vertical profile. We found that the clear-sky, instantaneous, SW DRF at the TOA and the atmospheric forcing were equal to −112 and 33 W m -2, respectively, at 10:50 UTC that represented the time at which the volcanic plume radiative impact was the highest. The SW aerosol heating rate reached the peak value of 1.24 K day −1 at 12 km asl and decreased to −0.06 K day −1 at 11 km asl, at 10:50 UTC. The role of the aerosol load located up to about 7 km asl and the corresponding radiative impact has also been evaluated. Highlights: A volcanic plume was investigated about 400 km away from the emission source. Satellite images, LiDAR, and radiometers were used to characterize the volcanic plume. Direct radiative forcing and heating rate due to the volcanic plume were evaluated. A methodology based on both experimental and model findings was used. The role of the aerosol load located below the volcanic plume was also estimated.